Regional Economic Agglomeration and Trans-Sumatra Toll Road Development: A Network and Spatial Review - Hariyanto, Annisa Dira; Rendra Graha, Dimas Tri; Afrianto, Firman (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
Road and transportation networks play a crucial role in interregional connections. One of the key development programs initiated during President Jokowi’s presidency in Indonesia is aimed at improving interregional connectivity. In Sumatra, the National Strategic Project (Program Strategis Nasional/PSN) for the construction of the Trans-Sumatra Toll Road has been underway since 2014. After a decade of development, it is essential to evaluate the impact of this infrastructure on the region's agglomeration to inform future development policies. This paper reviews the changes in network structures and economic activities as influenced by the construction of the Trans-Sumatra Toll Roads. It also seeks to predict the future development of agglomeration and economic activities. The study employs regional and city planning methodologies, including space syntax, fractal dimension analysis, and cluster analysis. The findings indicate that the construction of the Trans-Sumatra Toll Road has significantly enhanced connectivity and accessibility, increased the gravitational value of the territory, and reduced the load on existing roads. Moreover, the development of toll roads has led to the growth of new economic centers, which eventually resulted in the formation of four major agglomeration regions.